ALTERATIONS IN KNOWLEDGE, ATTITUDE, AND BEHAVIOURAL PATTERNS OF DENTISTS IN CIMAHI, INDONESIA REGARDING DENTAL MEDICAL WASTE MANAGEMENT POST COVID-19 PANDEMIC - Hartman, Henri; Arifianti, Isti; Irawan, Zidhan (Fakultas Kedokteran Gigi Unjani, 2024)
Management of dental medical waste is essential in preventing the spread of diseases, especially during the COVID-19 pandemic. The COVID-19 pandemic has increased the amount of medical waste in healthcare facilities, including dental practices. This study aims to determine the changes in dentists' knowledge, attitudes, and behaviours regarding the management of dental and medical waste after the COVID-19 pandemic. The research used a survey with an observational analytical approach, quantitative methods, and a cross-sectional research design. The research sample or respondents were 50 dentists practising independently in Cimahi. Data collection used questionnaire about dentists' knowledge, attitudes, and behaviours regarding managing dental and medical waste before and after the COVID-19 pandemic. The results of the Wilcoxon non-parametric test showed that the knowledge and attitudes of dentists regarding the management of dental medical waste after the COVID-19 pandemic experienced significant changes statistically (p < 0.05). However, dentists' behaviour in managing dental and medical waste did not show substantial statistical changes (p > 0.05). The study results concluded that the COVID-19 pandemic has positively impacted increasing dentists' awareness of the importance of managing medical waste. However, reinforcement is needed to maintain the good behaviour of dentists in managing dental medical waste. DOI : 10.54052/jhds.v4n1.p69-80